Antimicrobial Resistance in Commensal Escherichia coli of the Porcine Gastrointestinal Tract - Lorcan O'Neill; Edgar García Manzanilla; Daniel Ekhlas; Finola C. Leonard (MDPI AG, 2023)
Antimicrobial resistance (AMR) in Escherichia coli of animal origin presents a threat to human health. Although animals are not the primary source of human infections, humans may be exposed to AMR E. coli of animal origin and their AMR genes through the food chain, direct contact with animals, and via the environment. For this reason, AMR in E. coli from food producing animals is included in most national and international AMR monitoring programmes and is the subject of a large body of research. As pig farming is one of the largest livestock sectors and the one with the highest antimicrobial use, there is considerable interest in the epidemiology of AMR in E. coli of porcine origin. This literature review presents an overview and appraisal of current knowledge of AMR in commensal E. coli of the porcine gastrointestinal tract with a focus on its evolution during the pig lifecycle and the relationship with antimicrobial use. It also presents an overview of the epidemiology of resistance to extended spectrum cephalosporins, fluoroquinolones, and colistin in pig production. The review highlights the widespread nature of AMR in the porcine commensal E. coli population, especially to the most-used classes in pig farming and discusses the complex interplay between age and antimicrobial use during the pig lifecycle.